Persepsi Siswa Terhadap Kompetensi Sosial Guru di Sekolah Menengah Kejuruan - Safitri, Nadia; Hanif Alkadri (Global Action and Education for Society, 2023)
This research is motivated by the results of the author's observations while carrying out Educational Field Practices at SMKN 6 Padang which show the low social competence of teachers. The research questions are 1) How able are teachers to communicate at school based on students' perceptions of SMK Negeri 6 Padang, 2) How able are teachers to get along effectively in schools based on students' perceptions of SMK Negeri 6 Padang, 3) How capable teachers are in using technology and information functionally based on students' perceptions of SMK Negeri 6 Padang. This research is a quantitative descriptive study, the population of this research is students of SMK Negeri 6 Padang, totaling 972 people, and sampling was carried out using proportional random sampling technique with the Slovin formula and obtained a sample of 100 people. The data collection tool is a questionnaire with a Likert Scale model, and for testing the validity and reliability of the questionnaire it is assisted by using the SPSS 28.0 application. Data analysis techniques use the average formula (mean). The results showed that students' perceptions of the social competence of teachers at SMK Negeri 6 Padang, seen from the following aspects: (1) the ability of teachers to communicate is in the capable category with an average score of 3.77; (2) the ability to get along effectively with students is in the very capable category with an average score of 4.22; (3) the ability to use technology and information functionally is in the quite capable category with an average score of 4.05. Overall it can be concluded that students' perceptions of teacher social competence are in the capable category with an average score of 3.50. This means that students' perceptions of the social competence of teachers at SMK Negeri 6 Padang are in the capable category.